1990
DOI: 10.1126/science.248.4959.1093
|View full text |Cite
|
Sign up to set email alerts
|

Venting of Carbon Dioxide-Rich Fluid and Hydrate Formation in Mid-Okinawa Trough Backarc Basin

Abstract: Carbon dioxide-rich fluid bubbles, containing approximately 86 percent CO(2), 3 percent H(2)S, and 11 percent residual gas (CH(4) + H(2)), were observed to emerge from the sea floor at 1335- to 1550-m depth in the JADE hydrothermal field, mid-Okinawa Trough. Upon contact with seawater at 3.8 degrees C, gas hydrate immediately formed on the surface of the bubbles and these hydrates coalesced to form pipes standing on the sediments. Chemical composition and carbon, sulfur, and helium isotopic ratios indicate tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
182
1
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 296 publications
(194 citation statements)
references
References 9 publications
10
182
1
1
Order By: Relevance
“…The highest CO 2 concentrations, found in the lower Cl fluids at Snowcap and Satanic Mills (Fig. 5.5b, Table 5.2), are among the highest reported to date for vent fluids (Karl et al, 1988;Butterfield et al, 1990;Sakai et al, 1990a,b;Von Damm, 1995;German and Von Damm, 2003;Lupton et al, 2006) and are comparable to those observed in black smoker fluids at the back-arc JADE site, Okinawa Trough (Sakai et al, 1990b). In addition to the higher concentrations relative to Vienna Woods, CO 2 is more 13 C-enriched at PACMANUS, with endmember δ 13 C CO2 values varying from -4.1‰ to -2.3‰ (Table 5.2).…”
Section: H 2 H 2 S Ch 4 Co and Cosupporting
confidence: 54%
See 1 more Smart Citation
“…The highest CO 2 concentrations, found in the lower Cl fluids at Snowcap and Satanic Mills (Fig. 5.5b, Table 5.2), are among the highest reported to date for vent fluids (Karl et al, 1988;Butterfield et al, 1990;Sakai et al, 1990a,b;Von Damm, 1995;German and Von Damm, 2003;Lupton et al, 2006) and are comparable to those observed in black smoker fluids at the back-arc JADE site, Okinawa Trough (Sakai et al, 1990b). In addition to the higher concentrations relative to Vienna Woods, CO 2 is more 13 C-enriched at PACMANUS, with endmember δ 13 C CO2 values varying from -4.1‰ to -2.3‰ (Table 5.2).…”
Section: H 2 H 2 S Ch 4 Co and Cosupporting
confidence: 54%
“…Trends of increasing δ 13 C CO2 with arc proximity have been observed in other back-arc vent fluids, such as the Lau Basin (Proskurowski et al, 2006) and the Okinawa Trough/Mariana Arc (cf. Sakai et al (1990b) and Lupton et al (2006)). …”
Section: Magmatic Co 2 F and CLmentioning
confidence: 99%
“…Diffusive shimmering vents and inactive chimneys have been recognized, along the active venting, in a NE-SW direction . Emission of liquid CO 2 was identified at both extensions of the chimney line (Sakai et al 1990). At the southwestern extension of the chimney line, thick layered consolidated structure plausibly consisted of amorphous silica and native sulfur was recognized at~500 m apart from the TBS chimney.…”
Section: Jade Hydrothermal Field In the Izena Holementioning
confidence: 92%
“…The main difference from rocky fauna is that most sedimentary fauna are shared between methane seep sites in Sagami Bay and Nankai Trough (Watanabe et al 2010). This can be attributed to the similarity of vent fauna in the Okinawa Trough to the methane seep fauna, in addition to the high concentration of methane and CO 2 in vent fluids (Sakai et al 1990). …”
Section: Faunal Zonation In a Vent Fieldmentioning
confidence: 99%